Appropriateness and yield of surveillance colonoscopy in first-degree relatives of colorectal cancer patients: A 5-year follow-up population-based study. Issue 5 (May 2018) - Armelao, Franco; Pertile, Riccardo; Miori, Gianni; Franch, Renzo; Avancini, Ivo; Meggio, Alberto; Franceschini, Gaia; Pravadelli, Cecilia; Tieppo, Chiara; Faitini, Katia; Giacomin, Davide; Orlandi, Pier Giuseppe; et al.
Abstract: Background and aims: There are few prospective data about the use of surveillance colonoscopy and the risk of recurrent neoplasia in first degree relatives (FDRs) of colorectal cancer (CRC) patients. We examined the use and yield of surveillance colonoscopy in a population-based screening program (Trentino, Italy) Methods: 1252 FDRs have been included in this study. We calculated compliance (percentage of FDRs who underwent surveillance colonoscopy among those eligible), appropriateness of colonoscopy (appropriate if performed within 6 months of the guidelines recommended interval) and diagnostic yield for neoplasia. We compared these data with those of 765 individuals without a family history (FH) of CRC who underwent screening colonoscopy in the same period (controls). Results: Compliance and appropriateness were higher in FDRs than in controls (93.0% vs. 48.0%; p < 0.001; 59.6% vs. 18.8%; p < 0.0001, respectively). Younger age, female sex, FH of CRC and both non-advanced adenomas (nAA) and advanced adenomas (AA) at screening colonoscopy were predictors of appropriate surveillance. The cumulative incidence of nAA and AA was similar in FDRs and controls (31.7% and 4.9% in FDRs, including three invasive cancers; 32.4% and 5.8% in controls, respectively). Conclusion: FH does not increase the risk of AA in a 5-year follow-up; appropriate surveillance practices in FDRs could be highly expected in an organized screening program.